Influence of graphene oxide on photocatalytic enhancement of cerium dioxide - Duangdao Channei (2018)
© 2017 Graphene oxide (GO) was prepared by oxidizing purified natural flake graphite via modified Hummers method. The suspension of GO particles and cerium-based precursors were treated hydrothermally in order to prepare CeO2/GO composites. The disappearance of the [0 0 1] GO diffraction peak was observable in the XRD pattern for CeO2/GO composites because the crystal growth of CeO2between the interlayer of GO destroyed the regular layer stacking of GO phase. However XPS spectra of O 1 s core level and oxygen vacancies defect in CeO2caused the decrease in degree of crystallinity. Composite of CeO2with GO not only prevented the formation of extrinsic vacancies in the oxygen sub-lattice, but also prevented the switching from the major photoactive species Ce4+to Ce3+.The photocatalytic activity measurements demonstrated that the CeO2/GO composites exhibited much higher photocatalytic activity than CeO2for degradation of methylene blue (MB) under visible light irradiation. The enhancement of photocatalytic activity could be attributed to the excellently elevated absorption ability for the MB dye through π–π conjugation. As reported in PL results, the effective inhibition of the recombination of photogenerated electron–hole pairs due to the charge interaction between CeO2and GO.